Análisis de resiliencia comunitaria ante factores climáticos extremos (precipitación, heladas, sequía, vientos) en las comunidades del Corazón, Culebrillas, Pachakutic de la parroquia de Guanujo cantón Guaranda provincia Bolívar en el periodo 2017 - Taris Tandalla, María Soledad (2017)
The present research work "Analysis of Community Resilience to extreme climatic factors (precipitation, frost, winds, drought), was intended to analyze community resilience to the meteorological factors, inhabitants should have knowledge and ability to respond immediately to any Factor that is present in order to reduce the impact of the risk. The methodology used was descriptive and exploratory the techniques used, observation in situ, survey and observation guide with which data were obtained for the information. The results obtained: absence of educational processes in risk management that generate community resilience, weak socio-organizational process; Extreme climatic factors affect the activities of agriculture and livestock in their order are frost, drought, precipitation and winds; The strategies of change are the application of UEB-community linkage process, infrastructure implementation management, community participation, socio-organizational strengthening and leadership as well as ancestral practices to deal with climatic factors. Conclusions The level of community resilience in the analyzed communities is minimal due to the absence of educational processes, weak organizational strengthening; High incidence of extreme climatic factors mainly in agriculture and livestock, with economic losses that influences living conditions.